ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN - Siti Yulia (MADINASIKA, 2021)
The research was motivated by the low quality of education was thought of suboptimal human resource development. The research aims to: a) Know the management of human resource development; b) Knowing the strategy for human resource development; c) Supporting factors and obstacles to human resource development; d) The efforts of the principal in overcoming obstacles to human resource development; e) The quality of education. The study used a qualitative approach with analysis methods, techniques and primary data collection tools using in-depth interviews with selected informants purposively. Data were analyzed descriptively interpretive through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) Human resource development has been carried out in accordance with the authority of the school principal; b) Human resource development strategies are planned carefully and accurately; c) The dominant supporting factor is the high enthusiasm of teachers to improve competence, but is hampered by the non-fulfillment of quantitative PNS teachers; d) To overcome obstacles, school principals recruit teachers who are honorary statuses; e) The quality of education has not been optimal, especially in meeting the eight educational standards. In conclusion, the development of human resources has been carried out well, but is hampered by the limitations of quantitative professional educators, so that the quality of education is not optimal.